(untitled) (African Journal of Biomedical Research, 2023)
Malaria during pregnancy is considered a serious public health challenge in tropical and subtropical regions. In 2020, there were an estimated 33.8 million pregnancies in the WHO African Region, of which 11.6 million (34%) were at risk of malaria infection during pregnancy, and the West African sub-region bears the highest prevalence (39.8%) of exposure to malaria during pregnancy. Due to the high prevalence of malaria infection among pregnant women, this study aimed to explore the pattern of malaria prevalence among pregnant women using clinically confirmed hospital data from 2014 to 2019 in Jigawa State, Northwest Nigeria. ArcGIS version 10.3 was used for database development and spatial data analysis. Spatial statistics namely Global Moran’s I and Local Getis-Ord statistics (Gi*) were used to conduct data analysis. The former was employed to detect the existence of clusters while the latter was used to show the location of clusters. Results show that there is a statistically significant cluster pattern of malaria prevalence from the year 2014 to 2018, while the year 2019 had a random distribution. The clustering was strongest in the year 2016 with Moran’s I 0.387680, Z-score 3.946283, and P value 0.000079. The detected hotspots concentrate in the central part of the study area while cold spots occurred in the northern part. The study suggests that proper attention should be given to hot spot locations in the allocation of resources for malaria control